Becoming an African Diaspora in Australia Language, Culture, Identity - Ndhlovu, Finex; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Becoming an African Diaspora in Australia uses new data on the identity formation process of migrant communities to rethink the vocabularies we use to look at language, culture and identity.
Keywords: Literature; Ethnology -- Africa; African literature; African languages; Applied linguistics; Sociolinguistics; Ethnicity; Applied Linguistics; African Culture; Ethnicity Studies